Village landscapes classified into social-ecological patches - Sinare, Hanna; D. Peterson, Garry; Börjeson, Lowe; J. Gordon, Line (Stockholm University, 2022)
The following .tif files are named with village
name and year, and are raster files where we have classified each 100x100 meter
cell of the village landscapes into SEPs through a visual, manual interpretation
of aerial photographs and satellite images in ArcGIS 10.3 software (ESRI 2013).
These files are read and analyzed using the R code for analysis of historic generation of ecosystem services in village landscapes [https://doi.org/10.17045/sthlmuni.19144616] and Tables for calculating change in generation of ecosystem services over time [https://doi.org/10.17045/sthlmuni.17032724]
Keywords: Agricultural land management; Agro-ecosystem function and prediction; Agroforestry; Sustainable agricultural development; Natural resource management; Agricultural Science; Jordbruksvetenskap; Other Agricultural Sciences; Annan lantbruksvetenskap